An Update on Etiology and Management of Recurrent Pregnancy Loss - Akhtar, Nahreen; Shahrin, Meem; Sayeeda, Syeda; Parveen, Tabassum (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Recurrent Pregnancy Loss (RPL) is a complex health challenge with no universally accepted definition. Incidence of recurrent miscarriage is reported to range from 1% to 3%. The exact etiology of recurrent pregnancy loss remains questionable; thus, it is considered a polyetiological and multifactorial condition with many modifiable and non-modifiable factors involved. Known risk factors for RPL are maternal age, previous pregnancy losses, parental chromosomal abnormalities, uterine morphological pathologies, endocrine disturbances, antiphospholipid syndrome (APS), inherited thrombophilia and infectious agents. However, even after thoroughly evaluating recurrent pregnancy loss etiology and risk factors, up to 75% of cases remain unexplained. This review aimed to summarize accumulated knowledge on the etiology, risk factors and management approach to recurrent pregnancy loss. Bangladesh J Obstet Gynaecol, 2023; Vol. 38(2): 96-102